2015
DOI: 10.1371/journal.pone.0121105
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Role of Common Interests in Online User Trust Formation

Abstract: Despite enormous recent efforts in detecting the mechanism of the social relation formation in online social systems, the underlying rules between the common interests and social relations are still under dispute. Do online users befriend others who have similar tastes, or do their tastes become more similar after they become friends? In this paper, we investigate the correlation between online user trust formation and their common interests, measured by the overlap rate ρ and taste similarity θ respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…In addition, we have not investigated the constitution of the types of users who select the objects with specific degree, which is a still an open question. Furthermore, it is important to verdict whether the information entropy could be considered in the recommender algorithms [30][31][32][33].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In addition, we have not investigated the constitution of the types of users who select the objects with specific degree, which is a still an open question. Furthermore, it is important to verdict whether the information entropy could be considered in the recommender algorithms [30][31][32][33].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Individuals are always engage in group life and the interactions between friends are more frequent than that of crowds. Thus, it it very common that people behave similar to their friends (Lewis et al, 2012;Ji et al, 2015). Yet, different friends may have different impact over a specific consumer.…”
Section: Friend Impact Versus Crowd Impact On Consumer Posting Behaviourmentioning
confidence: 99%
“…As we discussed in section 3.1, a large volume of the crowd review may suggest that the business is of common interest for most of consumers, while the volume of friend review can indicate the interest of the target consumer's local social group. Since friends normally have similar interests, tastes and so on (Ji et al, 2015;Pan et al, 2017;Leskovec et al, 2007), a consumer is more likely to select these businesses of his/her friends' interests (high volume of friend reviews), rather than those of common interests (high volume of crowd reviews). A higher chance of getting consumed will lead to higher possibility of being reviewed.…”
Section: Review Volumementioning
confidence: 99%
“…Furthermore, Ni and Wang et al [26,27] found that small-degree users tend to select popular movies, while large-degree users prefer to select the unpopular ones. The heterogeneous physics of the object popularity plays an important role for the online social systems evolution [28,29]. As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%